THE EFFECT OF DISCRETIONARY AND NON-DISCRETIONARY INCOME SMOOTHING AND CAPITAL BUFFER ON CREDIT GROWTH: MODERATED BY LIQUIDITY RISK - Yudi Yudi; Sistya Rachmawati (Universitas Pakuan, 2025)
ABSTRACTThis study aims to examine the effect of discretionary and non-discretionary income smoothing and capital buffers on credit growth, moderated by liquidity risk. This study uses data regression analysis with a fixed-effects model. The study sample consisted of 170 respondents, consisting of 36 banking companies listed on the Indonesia Stock Exchange from 2020 to 2024. The results of this study show a significant positive effect of discretionary and non-discretionary income smoothing and capital buffers on credit growth. Liquidity risk has no effect on credit growth, and the interaction with discretionary income smoothing has been proven to strengthen this effect, indicating as quasi-moderation. However, when liquidity risk interacts with non-discretionary income smoothing and capital buffers, the interaction is proven not to strengthen the effect, indicating as predictor moderation. Originality this study offers important insights for regulators and practitioners regarding the impact of income smoothing and capital buffers in controlling credit growth during the COVID-19 pandemic.ABSTRAKPenelitian ini bertujuan untuk menguji pengaruh perataan laba diskresioner, dan non-diskresioner dan modal penyangga terhadap pertumbuhan kredit bank yang dimoderasi oleh risiko likuiditas. Penelitian ini menggunakan analisis regresi data dengan fixed effect model. Sampel penelitian ini sebanyak 170 terdiri dari 36 perusahaan perbankan yang terdaftar di Bursa Efek Indonesia dari tahun 2020 hingga 2024. Hasil studi ini membuktikan adanya pengaruh positif signifikan perataan laba diskresioner dan non-diskresioner dan modal penyangga terhadap pertumbuhan kredit. Risiko likuiditas tidak berpengaruh terhadap pertumbuhan kredit, namun setelah diinteraksikan dengan perataan laba diskresioner, terbukti memperkuat, yang disebut sebagai kuasi moderasi. Risiko likuiditas diinteraksikan dengan perataan laba non-diskresioner dan penyangga modal, terbukti tidak memperkuat, yang disebut sebagai moderasi prediktor. Orisinalitas studi ini menawarkan wawasan penting bagi regulator dan praktisi tentang dampak perataan laba dan modal penyangga dalam mengendalikan pertumbuhan kredit masa pandemic covid-19